Effects of correlated noises on binocular rivalry. (June 2022) - Chen, Ruyin; Xiong, Yue; Li, Zekun; He, Zhifen; Hou, Fang; Zhou, Jiawei
Abstract: Visual pathways are inherently stochastic and thus noisy. Such fluctuation is generally considered to be a nuisance, actually, it shows potential benefits to perceptual alteration. Here, we investigated binocular rivalry subjected to correlated noises (correlation between additive noise and multiplicative noise). Our numerical results reveal that: (i) Noise enhanced stability phenomenon appears for the correlated case, while vanishes for the uncorrelated case; (ii) Multiplicative noise intensity presents very limited impact on the perceptual alternation under some certain additive noise intensities; (iii) Coherence resonance takes place for negative correlation, while disappears for positive or non correlation; (iv) Imbalance of perceptual dominance, caused by the correlation strengthen difference between the eyes, weakens the perceptual stability, but it has beneficial effects for inducement of coherence resonance. These findings have the significant implication for a deeper understanding of rivalry and its relationship to binocular vision. PACS numbers: 02.50.-r, 05.40.-a, 87.10.-e